Spoilage potential of Paenibacillus sp. in Brazilian raw milk - José Carlos Ribeiro Júnior (Ciência Rural, 2016)
Bacterial spores are widespread in the environment and can contaminate milk. Spores are resistant to thermal conditions and your germination reduces milk shelf-life because the aerobic bacteria that are sporulated produce proteases and lipases. The aim of this study was identify Paenibacillus sp., the spoilage microbiota, arising from the germination of spores in raw milk and your spoilage potential. Twenty different milk samples were treated at 80°C/12min and plated to isolate spore-forming bacteria. These strains were picked in milk agar and tributyrin agar for verification of their potential proteolytic and lipolytic activities, respectively. Amplification and sequencing of the 16S rRNA gene of the strains for identification by similarity to the DNA sequences deposited in GenBank was performed. One hundred and thirty-seven isolates were obtained, of which 40 (29.2%) showed spoilage activity for milk. Of these, three (7.5%) were identified as strains of Paenibacillus sp., and all were lipolytic. Paenibacillus sp. have been identified as primarily responsible for the spoilage of pasteurized milk with a long shelf-life in other countries. To increase the shelf-life of Brazilian pasteurized milk, it is important to identify the sporulated microbes to determine their origin and to control the contamination of milk by vegetative forms such as spores.